Pustakawan Universitas Islam Negeri Sumatera Utara menyongsong world class library - Habiba Noer Maulida (UIN Sumatera Utara, 2017)
This article discusses about The librarian of the Islamic university of north sumatera welcomes the world class library. To make the world class library, librarians should be able to use and utilize information technology in the library. In order to process and present all-digital information to users of information services. This is done in accordance with the increasingly modern era in applying information technology.Keywords: Librarian, world class library, information technology